Appearance of V-encapsulated tetragonal prism motifs in VSi10− and VSi11− clusters. Issue 40 (8th October 2020) - Zhang, Li-Juan; Yang, Bin; Li, Da-Zhi; Farooq, Umar; Xu, Xi-Ling; Zheng, Wei-Jun; Xu, Hong-Guang
Abstract : A novel tetragonal prism unit is observed in VSi10 − and VSi11 − clusters, offering new ideas in developing components for Si-based nanodevices. Abstract : The structural and electronic properties of V-doped silicon clusters, VSi10 −/0 and VSi11 −/0, were investigated by using mass-selected anion photoelectron spectroscopy in combination with theoretical calculations. Photoelectron spectroscopy of VSi10 − and VSi11 − clusters with spectral similarity reveals that the two cluster structures resemble each other. Interestingly, theoretical calculation studies provide definitive evidence of the global minima for the two clusters to be V-encapsulated tetragonal prism motifs with extra Si atoms bicapped and tricapped, respectively. The enhanced stability of the tetragonal prism unit in VSi10 − and VSi11 − is due to the strong interactions between 3d (V) and 3p (Si) orbitals, and more charge transfers from the Si n framework to the encapsulated V atom. The tetragonal prism unit possessed by both the VSi10 − and VSi11 − clusters is observed for the first time in the current work, and may offer new ideas in developing components for Si-based nanodevices.